High tolerance of the superconducting current to large grain boundary angles in potassium-doped BaFe2As2 - Takafumi Hatano; Dongyi Qin; Kazumasa Iida; Hongye Gao; Zimeng Guo; Hikaru Saito; Satoshi Hata; Yusuke Shimada; Michio Naito; Akiyasu Yamamoto (NPG Asia Materials)
Abstract Superconducting magnets based on high-temperature superconductors (HTSs) have become critical components in cutting-edge technologies such as advanced medical applications. In HTSs, weak links of superconductivity are inevitable at high-angle grain boundaries (GBs). Thus, two adjacent grains should be crystallographically aligned within the critical angle (θ c), for which the intergrain critical current density (J c) starts to decrease exponentially. The θ c of several iron-based superconductors (IBSs) is larger than that of cuprates. However, the decreases in both θ c and intergrain J c under magnetic fields for IBSs are still substantial, hampering their applications in polycrystalline forms. Here, we report that potassium-doped BaFe2As2 (Ba122:K) exhibits superior GB performance to that of previously reported IBSs. A transport J c of over 0.1 MA/cm2 across [001]-tilt GBs with misorientation angles up to θ GB = 24° was recorded even at 28 K, which is a required level for practical applications. Additionally, even in an applied magnetic field, θ c was unaltered, and the decay of the intergrain J c was small. Our results highlight the exceptional potential of Ba122:K for polycrystalline applications and pave the way for next-generation superconducting magnets.